Role of temperament and communication in conflict management styles: A conceptual approach - Musah, A.A. (American Scientific Publishers, 2015)
This paper examines relationship between temperament and communication in conflict management styles in organizations by identifying inert factors underlying conflict behavior. Traditional conflict research assumes that when individuals face conflicts they follow a rational process, thus denying the role of emotion-relevant variables. The paper develops a conceptual model based on past literature and research to explain the role of temperament and communication in choice of conflict management styles. The model brings a new perspective to the issue of interpersonal conflict in work groups. Recognizing and understanding the role of temperament and communication in conflict management will help manage âhuman issuesâ in organizations. By understanding and appreciating differences in individuals, team members can achieve better work performance. The paper contends that poor understanding of temperament central in human interaction will deter organizational efforts to accomplish a cohesive work teams and to promote appreciation in the workplace and beyond. The paper further asserts that improving peoples understanding of temperament and how they manifest in attitudes and behaviors will help manager/supervisors and employees to relate more effectively, personally as well as professionally. This paper provides a new way of looking at managing conflict by highlighting other determinants of conflict management styles apart from the generic ones. Â© 2015 American Scientific Publishers. All rights reserved.